Effect of Earning Per Share (EPS), Return on Asset (ROA), and Return on Equity (ROE) on Stock Price in the Indonesia Stock Exchange - Hidayat Darwis; Abdullah Nasir (Journal of Business, Management, & Accounting, 2021)
The decision to invest in a company's shares is determined from an analysis of the company's performance. This analysis is expected to measure the stock price of a company in the future. The analysis used to measure the company's performance in this study is Earning Per Share (EPS), Return On Assets (ROA), and Return on Equity (ROE). This study was conducted to test and obtain empirical evidence of the effect of EPS, ROA, and ROE on stock prices. The research method used is descriptive statistics, classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, and hypothesis testing with multiple regression analysis, coefficient of determination, partial t test, and simultaneous f test. The results showed that not all hypotheses can be accepted. The results show that Earning Per Share (EPS) has a positive and significant effect on the company's stock price, Return On Assets (ROA) has no significant effect on the company's stock price, Return On Equity (ROE) has a negative and significant effect on stock prices. company. In addition, the results also show that Earning Per Share (EPS), Return On Assets (ROA), and Return On Equity (ROE) together have a significant influence on the company's stock price. Therefore, investors need to pay attention to Earning Per Share (EPS), Return On Equity (ROE), and Earning Per Share (EPS), Return On Assets (ROA), and Return On Equity (ROE) together to measure stocks that will be purchased.